2019
DOI: 10.1017/s0144686x19000503
|View full text |Cite
|
Sign up to set email alerts
|

Who does not intend to retire? Mothers' opportunity costs and compensation at later ages in Europe

Abstract: Research investigating the association between women's work–family trajectories and their retirement intentions is limited. Studies considering how different institutional conditions affect this association are even more limited. To fill this gap, we use the first three waves of the Survey of Health, Ageing and Retirement in Europe, 2004–2009, and apply two-level random effects models with country-level fixed effects to a sample of mothers aged 50–64 years. Our dependent variable is the intention to retire as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…The lack of statistical significance is surprising, as mothers who delay family formation are expected to have more time to invest in their human capital prior to motherhood, which should increase their employment chances after family formation or even their opportunities to stay attached to the labour market during their childbearing years (Florian, 2018a;Gough & Noonan, 2013;Muller et al, 2020). Moreover, delaying childbirth (or marriage) is often seen as an indicator for strong attachment to paid work (Hank, 2004;Y. Kim & Rizzi, 2020;Pienta et al, 1994) as previous studies find that a strong attachment to paid work delays marriage and fertility (Koelet et al, 2015;Sun & Chen, 2017;Wood et al, 2016).…”
Section: Journal Of Family Studiesmentioning
confidence: 99%
“…The lack of statistical significance is surprising, as mothers who delay family formation are expected to have more time to invest in their human capital prior to motherhood, which should increase their employment chances after family formation or even their opportunities to stay attached to the labour market during their childbearing years (Florian, 2018a;Gough & Noonan, 2013;Muller et al, 2020). Moreover, delaying childbirth (or marriage) is often seen as an indicator for strong attachment to paid work (Hank, 2004;Y. Kim & Rizzi, 2020;Pienta et al, 1994) as previous studies find that a strong attachment to paid work delays marriage and fertility (Koelet et al, 2015;Sun & Chen, 2017;Wood et al, 2016).…”
Section: Journal Of Family Studiesmentioning
confidence: 99%
“…Because of their lower earnings, women may be more vulnerable in the case of divorce. Moreover, in the long term, work time reduction may affect pension income (Kim and Rizzi, 2019). The Belgian family policy system takes women's work time reduction into account when calculating the pension amount in the case of leave and time credit use.…”
Section: Concluding Discussion: Does Belgian Policy Support Fertility...mentioning
confidence: 99%
“…For older individuals, the Dutch policy compensates for work time reduction during one's earlier career by allowing a basic pension income corresponding to approximately 25% of average earnings. A basic pension system of more than 20% of average earnings is also applied in Sweden (Kim and Rizzi, 2019).…”
Section: • the Impact Of Time Reduction On Pensionmentioning
confidence: 99%
“…Some studies in Britain and the USA suggest that spending more years in employment during one's working life is associated with working beyond SPA for women but that this matters little for men (Pienta et al , 1994; Cahill et al , 2012; Finch, 2014; Stafford et al , 2019); but other studies in Switzerland and the USA report that both women and men with interrupted labour market histories are more likely to work in their fifties and sixties, especially among younger cohorts (Raymo et al , 2011; Clarke et al , 2012; Madero-Cabib et al , 2015). Kim and Rizzi (2020), using longitudinal European data, found that among women aged 50–64 (that is, those born between 1940 and 1957), it was those whose histories were characterised by interruptions and part-time work who intended to work for longer (Kim and Rizzi, 2020). Thus, a lack of clarity remains with respect to the relationship between women and men's labour market histories and paid work in the years up to and beyond SPA, especially once other contemporaneous factors are considered.…”
Section: Introductionmentioning
confidence: 99%